Hypidone Hydrochloride (YL-0919) Produces a Fast-Onset Reversal of the Behavioral and Synaptic Deficits Caused by Chronic Stress Exposure - Ran, Yuhua; Jin, Zengliang; Chen, Xiaofei; Zhao, Nan; Fang, Xinxin; Zhang, Liming; Zhang, Youzhi; Li, Yunfeng (Frontiers in Cellular Neuroscience, 2018)
Our precious study identified that Hypidone hydrochloride (YL-0919) as a novel dual 5-HT1A partial agonist and serotonin reuptake inhibitor exerts a significant antidepressant effect in various animal models. The aim of present research was to further investigate the fast-onset antidepressant effect and their underlie mechanisms. In current study, Sucrose preference test(SPT) were applied to test the fast-onset actions of YL-0919(2.5mg/kg p.o) on depressant-like behavior rats induced by chronic unpredictable stress(CUS) animal model. To determine how the mammalian target of rapamycin(mTOR) signaling involved in the fast-onset antidepressant-like effect of YL-0919, intracerebroventricular (i.c.v) with mTOR specific inhibitor rapamycin was combined given with YL-0919. Besides the behavior tests, the effects of YL-0919 on synaptosis-related protein expression were also evaluated. It has demonstrated that days treatment with YL-0919，but not FLX, rapidly increased SPT in CUS-induced rats and this effect can be abolished by co-treatment (icv) with rapamycin.YL-0919 treatment 5 days decreased the immobility time by FST and 10 days treatment decreased the latency to feed by NSFT on CUS-induced rats, which was also reversed by rapamycin respectively. Meanwhile, we also found that YL-0919 could significantly enhance the expression levels of synaptic proteins such synapsin I, PSD95, phosphorate-mTOR (pmTOR), BDNF in the hippocampus and that these effects could reversed by rapamycin. These data suggest that YL-0919 is a potential and potent fast-onset antidepressant. This fast-onset antidepressant of YL-0919 was partially involved with synaptogenesis mediated by activation of mTOR pathway.